Spectroscopic Analysis of the Romanian Icon "The Entry of the Lord into Jerusalem" by Grigore Ranite. (22nd January 2023) - Udrea, I.; Marutoiu, C.; Nemes, O. F.; Bratu, I.; Nemes, D.; Toader, D.
Abstract: The purpose of this study was to identify and characterize the painting materials and artistic technique used by Grigore Ranite to create the wooden icon, "The Entry of the Lord into Jerusalem." Particular attention was dedicated to identifying changes in the condition of the icon's materials. To achieve these aims, Fourier transform infrared spectroscopy in transmission-mode and X-ray fluorescence were used. The material used for the panel was identified to be softwood, which showed differing states of preservation due to wood-decay caused by fungi. It was established the multilayer structure of ground was composed of gypsum and animal glue. Ranite used the typical egg tempera (or tempera grassa) technique to obtain a polychromatic surface for the icon. The pigments that Ranite used to obtain the color red were vermilion, red lead, and hematite. For green, he used malachite, verdigris and copper resinate. Prussian blue and white lead, were probably employed for the color blue. Bone black pigments and iron oxides of various colors were also used. The varnish consisted mainly of a mixture of diterpenic resins, linseed oil, beeswax, and shellac. A major achievement was the identification of an early eighteenth century type of Prussian blue and characterization of its aging process. The results help to date and authenticate Ranite's icon, as well as to establish proper conservation methods in Romania. The findings will contribute toward a better understanding of the chemical and biological aspects of icon materials.